1995
DOI: 10.1111/j.1398-9995.1995.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms and immunologic reactivity to bee and wasp stings in beekeepers

Abstract: We compared the history of sting reactions with venom skin prick test (SPT) and CAP RAST reactions in beekeepers in order to assess the value of structured questions and symptom backgrounds. The study population consisted of 102 beekeepers, who were 25-75 years of age. Bee and wasp venom SPT was performed with concentrations of 10, 100, and 300 micrograms/ml. The CAP Phadiatop test was used in the screening of IgE antibodies against common inhalant allergens. Forty-two beekeepers had never experienced large lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…In the highly exposed population of beekeepers (Table 1), up to 31% report large local and 14-32% report systemic allergic reactions following bee stings [6][7][8][9][10][11][12]. In the highly exposed population of beekeepers (Table 1), up to 31% report large local and 14-32% report systemic allergic reactions following bee stings [6][7][8][9][10][11][12].…”
Section: Epidemiologymentioning
confidence: 99%
“…In the highly exposed population of beekeepers (Table 1), up to 31% report large local and 14-32% report systemic allergic reactions following bee stings [6][7][8][9][10][11][12]. In the highly exposed population of beekeepers (Table 1), up to 31% report large local and 14-32% report systemic allergic reactions following bee stings [6][7][8][9][10][11][12].…”
Section: Epidemiologymentioning
confidence: 99%
“…This fact has been confirmed by numerous studies reporting increased sensitisation after long term exposure, including increased sensitisation to hymenoptera venom in beekeepers, 4 to latex in hospital personnel, 5 and to laboratory animals' allergens in laboratory workers. 6 The aim of this study was to assess the prevalence of sensitisation to grapes, in a population with repeated exposure to grape allergens through direct cutaneous contact as well as through the gastrointestinal tract.…”
mentioning
confidence: 63%
“…8,12,13 However, until now, only case control retrospective study has been reported. 13,14 This is the first time that the pattern of sensitization development over a 5-year period was investigated in a follow-up prospective study, in a population starting occupational exposure to Hymenoptera venom, without previous sensitization and in comparison with a control group of people with outdoor occupational activities and occasional exposure to Hymenoptera venom.…”
Section: Discussionmentioning
confidence: 95%
“…Other published studies report atopic background in similar frequency among allergic beekeepers, allergic family members, and allergic controls. 11,12,13,16 Miyachi et al 17 observed a significantly higher frequency of atopic background in allergic beekeepers than in nonallergic beekeepers. They suggested that during their work, either through inhalation or multiple stings, atopic beekeepers are sensitized more easily than nonatopic beekeepers.…”
Section: Discussionmentioning
confidence: 96%